Analisis dan Perancangan Rangkaian Power Supply Dengan Modifikasi Penyearah Dioda IN4001 Untuk Mengatur Output Tegangan dan Arus Berdasarkan Variasi Beban - Saputra, Roni; Bintang Wahyu Hakim; Ahmad Rizalul Arifin (CV. Sekawan Siji, 2025)
This paper describes the analysis of a power supply circuit with a diode rectifier. Power supply has voltage and current variations when given different loads. So that the modification of the IN4001 type diode is applied to modify the output voltage and current based on the load. The research method is done by design and testing is done with Proteus simulation. The design results show that the rectifier modification and IN4001 diode modification produce significant differences in output current. The difference is shown as a current of 3.2A to 1.6A and a voltage of 220V to 7V. While the 200 Vdc supply voltage decreased by 110 Vdc, 180 Vdc decreased by 100Vdc, 160Vdc became 98Vdc, 140 became 85Vdc, 120 became 72 Vdc, 100 Vdc became 70 and 80Vdc became 60. Power supply with 1N4001 diode rectifier modification produces voltage and current variations that can be adjusted to adjust load variations. Power supply can be used for various types of voltage supply on other electronic devices that have changing loads.